2022
DOI: 10.1002/eap.2742
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mutualism: A promotional effect driven by bacteria during the early invasion of Phytolacca americana

Abstract: The enhanced mutualism hypothesis postulates that invasive plants promote self‐growth by enriching beneficial microbes to establish a positive soil feedback. However, the roles of soil microorganisms may vary with increasing time for plant growth. Research on changes in soil microbial communities over time has important implications for understanding the mechanisms underlying plant invasion. Due to the difficulty in evaluating the duration of plant growth, few studies have quantified the changes in soil microo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Initial invaders may promote the secondary invasion of subsequent species by facilitating mutualism (Meng et al., 2024; Zhang et al., 2020), gathering pathogenic fungi (Inderjit & van der Putten, 2010), and destroying the native mycorrhizal system and facilitating mutualistic integration (Hale et al., 2011; Stinson et al., 2006). Considering the soil bacteria, P. americana “gathered” a greater abundance of Streptomyces in the understory of R. pseudoacacia stand.…”
Section: Discussionmentioning
confidence: 99%
“…Initial invaders may promote the secondary invasion of subsequent species by facilitating mutualism (Meng et al., 2024; Zhang et al., 2020), gathering pathogenic fungi (Inderjit & van der Putten, 2010), and destroying the native mycorrhizal system and facilitating mutualistic integration (Hale et al., 2011; Stinson et al., 2006). Considering the soil bacteria, P. americana “gathered” a greater abundance of Streptomyces in the understory of R. pseudoacacia stand.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the enhanced mutualism hypothesis posits that invasive plants promote their own growth by enriching beneficial microbes in the soil, thereby establishing positive soil feedback. Meng et al (2023) found that plant growth‐promoting bacteria accumulated significantly in the soil during the early stages of Phytolacca americana invasions, and in turn the strength of enhanced positive feedback was likely to have facilitated P. americana invasions. This study highlights the evolving nature of plant–microbe interactions during biological invasions and underscores the role of bacteria in the initial success of P. americana invasions.…”
Section: Mechanisms Of Invasion Successmentioning
confidence: 99%
“…Invaders could also benefit from differences in plant-soil feedbacks that accumulate over time (Levine et al 2006). Plants experience negative feedbacks when a host-specific pathogen accumulates in the soil and suppresses their growth (Bever 2003, 2002), or positive feedbacks if the same dynamic occurs with a mutualist (Uddin et al 2021), and invading species have been observed to benefit from enhanced positive or reduced negative feedbacks in soils from their introduced ranges (Uddin et al 2021; Maron et al 2014; McGinn et al 2018; Meng et al 2024; Suding et al 2013; van der Putten et al 2013). Invaders might also benefit from interactions with a simplified microbial interaction network in a novel environment, allowing invaders to be more efficient in exploiting mutualists or defending against pathogens (Colautti and Lau 2015; Mesa and Dlugosch 2020).…”
Section: Introductionmentioning
confidence: 99%